Factors affecting pregnancy rates for goat embryos recovered and transferred by transcervical route - Morais, Maria Clara C.; Esteves, Luciana; Souza-Fabjan, Joanna M. G.; Oliveira, Maria Emilia F. [UNESP]; Silva, Marcio Roberto; Brandao, Felipe Z.; Fonseca, Jeferson F. (Elsevier B.V., 2020)
This study evaluated the factors affecting non-surgical embryo transfer (NSET) efficiency in goats. Donor goats (n = 10) were superovulated, mated and embryos were collected by non-surgical embryo recovery 7 d after estrous onset. A total of 28 pluriparous recipient goats were subjected to short-term progestagen-based estrous induction protocol with equine chorionic gonadotropin. They received 36 fresh embryos as single (n = 20) or in pairs (n = 8) by NSET 6-7 d after estrous onset, ipsilateral to the corpora lutea (CL). Pregnancy rate was affected (P < 0.05) by embryo stage (blastocyst = 63.6 % vs morulae = 24.0 %) and quality (Grade 1 = 57.1 %; 2 = 33.3 %; 3 = 10.0 %) and not (P > 0.05) by the uterine horn, number of CL (1-3), lactational status and number of embryos transferred per recipient goats. Both overall pregnancy and kidding rates were 32.1 % and 13 kids were born, representing an embryo survival rate of 36.1 %. Goat embryo transfer programs can be successfully performed by using non-surgical techniques, achieving satisfactory embryonic survival rates.
Keywords: Embryo quality; Goat; Transcervical embryo transfer